Effect of Rhodopseudomonas palustris as a Bioremediation on Reducing Ammonia and Nitrite Levels of Catfish Nursery Pond Water in District Kebakkramat Regency Karanganyar - Setyowati, Febriyanny Eka; Hutapea, Henny Parida (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
Catfish nursery pond water generally contains ammonia and nitrites. Ammonia and nitrite in this fish farming system start with uneaten catfish feed residue, feces, and metabolic products that enter the waters. Utilization of catfish feed which contains high protein can absorbed by fish as much as 20-30% of nutrients. The rest will be excreted in the form of feces. Feces and food scraps that settle in this water contain ammonia and nitrites, which affect the quality of the water. Efforts to maintain water quality are by reducing and disposing of pond water in the river. This is categorized as water pollution. Efforts to control this water pollution are the technique of bioremediation. The aim of bioremediation techniques is to restore the ecological balance in waters by utilizing microorganisms so that a process of degradation of harmful and complex compounds occurs into harmless compounds. The microorganisms used in this study were bacteria Rhodopseudomonas palustris which can to oxidize and decompose organic matter effectively reducing water quality. This research was conducted to examine the effect of bacterial efficiency Rhodopseudomonas palustris as a bioremediator for catfish pond water waste based on reducing levels of ammonia and nitrite. Testing the ammonia and nitrite levels using a spectrophotometric method with different wavelengths. Observations in this test were carried out for three days under anaerobic conditions and light at a temperature of 33Â°C. Observations showed that bacteria Rhodopseudomonas palustris had an effect on reducing nitrite levels 12.65% greater than the control. While the addition of bacteria to the observation of ammonia levels did not have a decreasing effect as indicated by the value F <F crit.